PENDAMPINGAN PENYUSUNAN PERATURAN DESA TENTANG PUNGUTAN DESA GUNA MENINGKATKAN PENDAPATAN ASLI DESA DI DESA BATUDULANG - Sri Nurhidayati; Darmanto Darmanto; Muhammad Salahuddin; Ardiyansyah Ardiyansyah; Amilan Hatta; Ade Sujastiawan; Edrial Edrial (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
Villages have autonomy to manage community interests through Village Regulations (Perdes), including the management of village levies as a source of Village Original Income (PADesa). Batudulang Village faced the obstacle of low PADesa, which only contributed 3.7% of total income in 2023. This community service activity aimed to assist the Batudulang Village Government in drafting the Village Levy Perdes. The method used was intensive mentoring through local potential identification, focus group discussions (FGD), and drafting regulations. The results of the activity showed the identification of various levy potentials including village property (buildings, fields), retributions (clean water, cleanliness), and administrative services (correspondence). This assistance successfully formulated the draft Batudulang Village Regulation on Village Levies which includes 10 chapters and an annex on the amount of levies. This regulation provides a strong legal basis to increase village financial independence in a transparent and accountable manner.